1995
DOI: 10.1038/ng0295-202
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model of X–linked chronic granulomatous disease, an inherited defect in phagocyte superoxide production

Abstract: Chronic granulomatous disease (CGD) is a recessive disorder characterized by a defective phagocyte respiratory burst oxidase, life-threatening pyogenic infections and inflammatory granulomas. Gene targeting was used to generate mice with a null allele of the gene involved in X-linked CGD, which encodes the 91 kD subunit of the oxidase cytochrome b. Affected hemizygous male mice lacked phagocyte superoxide production, manifested an increased susceptibility to infection with Staphylococcus aureus and Aspergillus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
779
3
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 848 publications
(820 citation statements)
references
References 34 publications
26
779
3
2
Order By: Relevance
“…Nox2 −/− mice on a C57BL/6J background (Pollock et al, 1995), originally obtained from Jackson Laboratories (Bar Harbour, USA), were bred from an established colony at Queen's University Belfast. Animal studies are reported in compliance with the ARRIVE guidelines (Kilkenny et al , 2010; McGrath and Lilley, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Nox2 −/− mice on a C57BL/6J background (Pollock et al, 1995), originally obtained from Jackson Laboratories (Bar Harbour, USA), were bred from an established colony at Queen's University Belfast. Animal studies are reported in compliance with the ARRIVE guidelines (Kilkenny et al , 2010; McGrath and Lilley, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Murine Lin À cells were isolated from bone marrow samples harvested from the femurs and tibias of B6.129S6-Cybb tm1Din/J mice, 49,50 (Ly5.2) using the Miltenyi Lineage Cell Depletion Kit (Miltenyi, Bergisch Gladbach, Germany) following the manufacturer's instructions. Lin À cells were cultured in StemSpan serum-free medium (StemCell Technologies, Grenoble, France) supplemented with 1% penicillin/streptomycin and cytokines.…”
Section: Cell Culturementioning
confidence: 99%
“…HSC from gp91 knockout male mice were transduced ex vivo and transplanted into gp91 knockout females. 20 Chimerism and proviral copy numbers were first determined at 5 weeks posttransplantation in the peripheral blood of the recipient animals and remained stable even at 6 months after the graft. At 8 weeks posttransplantation, levels of NADPH enzymatic activity were measured using the standard dihydrorhodamine (DHR) test.…”
Section: In Vivo Expression Of Most Promising Candidatesmentioning
confidence: 99%